Fingerprint reconstruction - Downie, Fiona (2012)
As fingerprints are used for identification purposes more and more these day how safe are they against a reconstructed fingerprint? Due to the methods that a person’s identity is stored on a biometric system there are ways from after obtaining this information that a fingerprint can be reconstructed and used for entry into the system. This report looks into two reconstruction method and if some of the aspects of the methods were changed how this would affect the acceptance into the security system. These aspects are whether the frequency of the binary ridges and the estimation of the orientation field for the reconstructed fingerprints make an impact to the falsely accepted rate of the reconstructed fingerprint. The second half of this report investigates the uses of third level features of fingerprints and their impact into the identification methods both for use in reconstructed fingerprints and for proving an identity of a person after a security breach.